Young people RFD Maine - Phippen, Sanford; Kennedy, Tami.; Rand, Janice; Gardner, Lisa.; Maine Public Television; United States. Rural Development ([Lewiston, Me.] : Maine Public Television, 1997)
Children learn about agriculture in a variety of hands-on ways. Maine Agriculture in the Classroom and Healthy Foods from Healthy Soils are just two of the ways teachers have found to get their students involved. And we hear from Danny Rodgers, a young fisherman from downeast, who thinks his rural way of life just can't be beat.
Program title from cassette label; program number from descriptive sheet.
Mini-series created by and originally broadcast on Maine Public Television. Funded by a television demonstration grant from Rural Development, part of the USDA. More information is availableon the WWW site: www.mpbc.org.
Segment producers: Lisa Gardner, Tami Kennedy, Janice Rand.
Hosted by Sandy Phippen.
VHS.
Closed captioned for the hearing impaired.
Keywords: Rural youth -- Maine; Education, Rural -- Maine; Documentary television programs -- Maine; Maine -- Rural conditions; Maine -- Social life and customs